Evaluation Models
X, 509 p.
Keywords: Evaluation Models is an up-to-date revision of the classic text first published in 1983. Organized in three sections, the first includes a historical perspective on the growth of evaluation theory and practice and two comparative analyses of the various alternative perspectives on evaluation. The second section includes articles representing the major schools of thought about evaluation written by the leaders who have developed these schools and models. The final section describes and discusses the Standards for Program Evaluation and the reformation of program evaluation.